인체 S100A2 단백질에 특이적인 단일클론 항체 - 김재화(Jae Wha Kim); 윤선영(Sun Young Yoon); 김주헌(Joo Heon Kim); 주종혁(Jong-Hyuck Joo); 김진숙(Jin Sook Kim); 이영희(Younghee Lee); 염영일(Young Il Yeom); 최용경(Yong-Kyung Choe); 최인성(In Seong Choe) (Immune network, 2003)
Background: The S100A2 gene, also known as S100L or CaN19, encodes a protein comprised of 99-amino acids, is a member of the calcium-binding proteins of EF-hand family. According to a recent study, this gene was over-expressed in several early and malignant carcinomas compared to normal tissues. To elucidate the role of S100A2 protein in the process during carcinogenesis, production of monoclonal antibody specific to the protein is essential. Methods: First, cDNA sequence coding for ORF region of human S100A2 gene was amplified and cloned into an expression vector to produce GST fusion protein. Recombinant S100A2 protein and subsequently, monoclonal antibody to the protein were produced. The specificity of anti-S100A2 monoclonal antibody was confirmed by immunoblot analysis of cross reactivity to other recombinant proteins of S100A family (GST-S100A1, GST-S100A4 and GST-S100A6). To confirm the relation of S100A2 to cervical carcinogenesis, S100A2 protein in early cervical carcinoma tissue was immunostained using the monoclonal antibody. Results: GST-S100A2 recombinant protein was purified by affinity chromatography and then fusion protein was cleaved and S100A2 protein was isolated. The monoclonal antibody (KK0723; Korean patent pending #2001-30294) to the protein was produced and the antibody did not react with other members of EF-hand family proteins such as S100A1, S100A4 and S100A6. Conclusion: These data suggest that anti-S100A2 monoclonal antibody produced in this study can be very useful for the early detection of cervical carcinoma and elucidation of mechanism during the early cervical carcinogenesis.